The impact of 16-h heat exposure on appetite and food reward in adults. (1st October 2022) - Charlot, Keyne; Millet, Juliette; Pasquier, Florane; Oustric, Pauline; Finlayson, Graham; Van Beers, Pascal; Monin, Jonathan; Sauvet, Fabien; Tardo-Dino, Pierre-Emmanuel; Malgoyre, Alexandra; ,
Abstract: Heat exposure is thought to reduce energy intake (EI) but studies are sparse and results not always concordant. The aim of this study was to examine whether a 16-h exposure to 32 °C leads to reduced EI compared to a control session (22 °C) and whether modifications in appetite sensations or food reward are implied. Sixteen healthy, lean, and active participants (9 women and 7 men, 25 ± 5 yo, body mass index: 22.0 ± 2.4 kg m −2 ) were passively exposed to two different thermal temperatures from 4:00 p.m. to 8:00 a.m. under controlled conditions. Hunger and thirst scores were regularly assessed using visual analogue scales. A fixed dinner meal (3670 ± 255 kJ) was consumed at 7:30 p.m. and an ad libitum breakfast buffet (20 foods/drinks varying in temperature, fat, and carbohydrate content) at 7:30 a.m. Components of reward (explicit liking [EL] and implicit wanting [EI]) for fat and sweet properties of food were assessed before each meal using the Leeds Food Preference Questionnaire (LFPQ). Ad libitum EI at breakfast did not differ between sessions (2319 ± 1108 vs 2329 ± 1141 kJ, in 22 and 32 °C sessions, respectively; p = 0.955). While thirst scores were higher in the 32 than the 22 °C session ( p < 0.001), hunger scores did not differ ( p = 0.580). EL and IW for high fat foods relative to low fat foods were decreased in 32 compared to 22 °C before dinner and breakfast ( p < 0.001 for all). Although EI and hunger were not affected by a 16-h exposure to heat, modifications in food reward suggested a reduction in the preference of high-fat foods. Future research should investigate whether reduced EI in response to heat exposure is due to spontaneous selection of low-fat foods rather than altered appetite sensations.